Do mal-estar à readaptação: o que causa o adoecimento e o afastamento da função docente. - Brand, Rita Melânia Webler (2013)
Education has been suffering huge changes in the last decades, affecting teachers' work with new forms of assessment and control, and the need to mastering new technologies. Consequently, human relations and psychophysical capabilities of teachers were affected, making them to do a great effort to fulfill their functions, leading many professionals to the discomfort and illnesses. The research emerges from the teaching experience of its author, having been developed with readapted teachers in Public School of the Regional EducationCenter (NRE) from Toledo (PR). Readapted teachers are those with physical or mental limitations, away from their work functions, by the medical expertise, to occupyother compatible features with their physical and / or psychic abilities. Seven teachers participated in this survey, including six women and one man, with ages between 44 and 62 years. Semi-structured interviews were conducted and field notes were taken, which characterizes the study as a qualitative research. The overall goal was to identify teachers in rehabilitation in the Schools from the NRE Toledo (PR) and, according to what they say, of what leads teachers to illness and rehabilitation. More specifically, the study aimed to examine: to what representationsteachers have readjusted themselves and their work; which allege that, in teaching, leads the faculty to the process of illness and rehabilitation; and if thereare gender differences in the processes by which teachers (men) and teachers (women) are readjusted. Theoretical discussions have their reasons, among other authors: Esteve (1999, 1995), addressing the teacher malaise, and Codo (1999), dealing with Burnout Syndrome, with contributions in analyzing the feelings of insecurity, fear, stress and wear these professionals face, causing suffering and absenteeism. The research shows a representation of teaching as a vocation, marked by nostalgia of teachers who believe they had authority, recognition and respect from the students, and today suffer from the loss of these values. They have difficulty in defining the profession itself and recognize teaching as work. A predominantly female profession, charged with attributes associated with motherhood, although among the interviewees just some realize the influences of gender in teaching. The school, in addition to being a place of knowledge production, would be diverted from their goals to other functions such as care, attention, affection, advice, providing necessities that families today do not keep pace. We conclude that the malaise is presented as a phenomenon of our time, affecting men and women in various professions, including teaching. This manifestation occurs from the physical and psychic wear in the subjects in their intense and constant relational work, which can lead to illness and, in several cases, to rehabilitation. Conflict labor relations, suffering and pain caused by the disease as a result of several years of professional activity may be triggering factors of rehabilitation. Means the malaise and The Burnout Syndrome will only be overcome by teachers when they learn to use coping strategies that help them to deal with the stress conditions at work. Moreover, public policies to ensure better working conditions and health are needed, so that teachers can exercise teaching with pleasure.